Continued training for Physical Education teachers: knowledge production analysis - Bagatini, Gabriela Zucki (2019)
This study aims to understand the Continuing Education in the Physical Education area. For that, was carried out a bibliographical review through online Brazilian magazines in the area of Physical Education, classified by Qualis in Physical Education, referred to as A1, A2, B1 and B2. In these journals, we searched for all the articles that debated the theme of Continuing Education, through the keyword Continuing Education. We have understood, among others, that Continuing Education is an inseparable practice of the school, and that should give this support to the teacher, as well as the possibility of a dialogue between theory and practice